Spatial distribution patterns and influencing factors of sports intangible cultural heritage in China - Kou, Wenhai; Zhai, Jiahao (Frontiers in Earth Science, 2025)
As an integral component of China’s intangible cultural heritage (ICH), sports intangible cultural heritage (SICH) holds immense significance and importance in cultural inheritance, social cohesion, health promotion, values education, cultural innovation. However, the spatial distribution characteristics and influencing factors of SICH have not been extensively explored. Therefore, we conducted an in-depth analysis of the spatial patterns and influencing factors of SICH utilizing Geographic Information System (GIS) spatial analysis methods such as geographic concentration index and kernel density estimation. The results reveal that SICH exhibits a spatially clustered distribution, with the highest concentrations in Hebei, Guangdong, and Zhejiang provinces. Notably, the Beijing-Tianjin-Hebei region and the Yangtze River Delta region are identified as areas with particularly high densities of SICH. The analysis of natural and human factors indicates that altitude, climate, rivers, GDP, and population density significantly influence the distribution of SICH, while the presence of core cities does not have a notable impact. This research provides valuable insights into the spatial distribution patterns of SICH and offers a foundation for future preservation and promotion strategies.